Oral Health Status in Subjects with Amnestic Mild Cognitive Impairment and Alzheimer's Disease: Data from the Zabút Aging Project - Panzarella, Vera; Mauceri, Rodolfo; Baschi, Roberta; Maniscalco, Laura; Campisi, Giuseppina; Monastero, Roberto (Journal of Alzheimer's disease, 2022)
The relationship between Alzheimer's disease (AD) and periodontitis has been recently investigated with heterogenous results. This study aims to evaluate the oral health status and its relationship with cognitive impairment of participants, enrolled in the Zabút Aging Project, a community-based cohort study performed in a rural community in Sicily, Italy. A case-control study (20 subjects with AD, 20 with amnestic mild cognitive impairment [aMCI], and 20 controls) was conducted. The protocol included a comprehensive medical and cognitive-behavioral examination. Full-mouth evaluation, microbial analysis of subgingival plaque samples (by RT-PCR analysis), and oral health-related quality of life (OHR-QoL) were evaluated. The decayed, missing, and filled teeth (DMFT) total score of AD subjects was significantly higher than aMCI (p = 0.009) and controls (p = 0.001). Furthermore, the "M" component of DMFT (i.e., the number of missing teeth) was significantly higher in AD than in aMCI (p < 0.001) and controls (p < 0.001). A Poisson regression model revealed that age (p < 0.001), male gender (p = 0.001), and AD (p = 0.001) were positively correlated with DMFT. Concerning oral microbial load, the presence of Fusobacterium nucleatum was significantly higher in AD than in controls (p = 0.02), and a higher load of Treponema denticola was found in aMCI than with AD (p = 0.004). OHR-QoL scores did not differ among the groups. The current research suggests that AD is associated with chronic periodontitis, which is capable of determining tooth loss due to the pathogenicity of Fusobacterium nucleatum. These data remain to be confirmed in larger population-based cohorts.